1989
DOI: 10.1113/jphysiol.1989.sp017567
|View full text |Cite
|
Sign up to set email alerts
|

An inwardly directed electrogenic sodium‐bicarbonate co‐transport in leech glial cells.

Abstract: SUMMARY1. We have used double-barrelled ion-sensitive microelectrodes to measure the intracellular pH, pHi, the intracellular Na+ activity, aiNa, and the membrane potential in identified glial cells of the central nervous system of the leech Hirudo medicinalis to study the effect of CO2-HCO3-.2. When a HEPES-buffered saline was exchanged for a saline buffered with 2 % CO2 +11 mM-HCO3-, keeping the pH constant at 7 4, the mean steady-state pHi ofthe glial cells increased from 6-85+0-06 to 7418+0-13 (mean+S.D., … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
123
1

Year Published

1993
1993
2008
2008

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 149 publications
(137 citation statements)
references
References 31 publications
(44 reference statements)
13
123
1
Order By: Relevance
“…Addition of 5 % C02-24 mm HC03-did not markedly alter the course of the membrane potential and al5, and decreased pHi by about 0 04 pH units. This indicates that external Na+ is needed to produce the potential and ion changes described previously upon addition of C02-HC03-(see also Deitmer & Schlue, 1989;Deitmer, 1992b). Changes of intracellular Na+ (a'a, lower trace), intracellular pH (pH,, middle trace) and membrane potential (Em, upper trace) during brief re-addition of Na+ to a Na+-free saline; Na+ was replaced by N-methyl-D-glucamine and records were made simultaneously with a triple-barrelled ion-sensitive microelectrode.…”
Section: Hco3-and Na+ Dependencesupporting
confidence: 52%
See 2 more Smart Citations
“…Addition of 5 % C02-24 mm HC03-did not markedly alter the course of the membrane potential and al5, and decreased pHi by about 0 04 pH units. This indicates that external Na+ is needed to produce the potential and ion changes described previously upon addition of C02-HC03-(see also Deitmer & Schlue, 1989;Deitmer, 1992b). Changes of intracellular Na+ (a'a, lower trace), intracellular pH (pH,, middle trace) and membrane potential (Em, upper trace) during brief re-addition of Na+ to a Na+-free saline; Na+ was replaced by N-methyl-D-glucamine and records were made simultaneously with a triple-barrelled ion-sensitive microelectrode.…”
Section: Hco3-and Na+ Dependencesupporting
confidence: 52%
“…1, and Deitmer & Schlue, 1989). When the glial membrane potential is clamped near its resting level (-65 to -75 mV), an outward current is recorded upon addition of C02-HC03- (Fig.…”
Section: Hco3-and Na+ Dependencementioning
confidence: 96%
See 1 more Smart Citation
“…In 1989, Deitmer and Schlue described an inwardly d irected electrogenic Na/HCO 3 cotransporter in leech glial cells [19]. Based on known va lues of [ Na + ] i , pH i and V m , they concluded that the stoichiometry must be 1:2.…”
Section: Electrogenicmentioning
confidence: 99%
“…Ischemia, lack of blood flow, leading to lack of oxygen has been shown to produce 4 mM increases in the intracellular 23Na concentration of cells [12]. Lack of oxygen in a cell forces it to produce lactic acid which decreases the intracellular pH.…”
Section: Physiology Of Sodium Ionsmentioning
confidence: 99%